IMPLEMENTATION OF THE PANCASILA VALUES TOWARDS IMPLEMENTATION OF THE MERDEKA CURRICULUM IN INDONESIAN EDUCATION SYSTEM - Pristi Suhendro Lukitoyo; Nuraini Br Sembiring; Riyan Kurniawan (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2023)
The research background can be seen from the curriculum which continues to experience changes as a result of the very rapid progress of the times, especially in the Indonesian education system which must be in harmony with the values of Pancasila, namely, in order to develop oneself in terms of abilities, skills, ethics and morals. In research reports, the authors apply qualitative research methods that use literature library research (literature study) where researchers take secondary data sources to collect related information about subjects and issues with data analysis techniques from the Miles and Huberman model, namely using qualitative data analysis. In the national education system, Pancasila values are nationally placed as a guideline for achieving educational goals, the system that refers to the implementation components is the 1945 Constitution and Pancasila which is used as the foundation of the state education system. As a consequence of improvements related to the addition of the previous curriculum, instructions for implementing the Merdeka Curriculumwere given as part of learning recovery (recovery of learning), as stated in Kemendikbudristek Decree No. 56 of 202. Based on this, the author tries to provide additional knowledge about the current education system which implements Pancasila values in implementing the Merdeka Curriculum. Merdeka Learning must be able to liberate students, educators, and educational institutions in a more effective system to advance the quality of education in Indonesia.